Why should Sub-Saharan Africa care about the Doha Development Round? - Peter Draper; Andreas Freytag; Sarah Al Doyaili (Economics: The Open-Access, Open-Assessment E-Journal, 2013)
In recent years sub-Saharan Africa, notwithstanding the global financial crisis, has increased its share in global trade and investment flows. This has led to an appreciable improvement in development levels, albeit off a small base. However, these patterns are still dominated by commodity flows and investment, and remain marginal on the global stage. Increased trade and investment flows, particularly related to network services, would be of great benefit to the sub-continent. Yet many domestic regulatory constraints remain. Furthermore, substantial international market distortions, particularly in agricultural trade, inhibit economic diversification into more value-adding activities. The Doha development round could, if concluded, go a long way towards addressing these barriers. Ultimately it could prove more consequential to the sub-continent's development trajectory than regional economic integration. The latter, whilst important, is shallow and too reliant on institution-intensive forms mimicking the European Union. Overall therefore this paper motivates for an African trade agenda focused on concluding the Doha round.
Keywords: F13; O10; O24; 330; Sub-Saharan Africa; Doha Development Agenda; international trade; commodities; agriculture; foreign direct investment; Außenhandelsliberalisierung; Entwicklungshilfe; Afrika südlich der Sahara